Analyzing the Social Mechanisms Regulating the Use of Dietary Supplements and Performance Enhancers Among Young Iraqi Weightlifters - Mukheef Fatlawi, Salih Mahdi; Zahedi, Hamid; Shaboot Ibrahim, Ali; Badami, Rokhsareh (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective:  The aim of this study was to analyze the social mechanisms associated with the use of dietary supplements and performance enhancers among young Iraqi weightlifters.Materials and Methods: This research utilized a descriptive-correlational design conducted through a survey method. The statistical population consisted of 376 active weightlifters from 17 cities in Iraq during 2023–2024, out of which 324 participants were selected using proportional stratified random sampling. To measure the variables under investigation, a researcher-designed questionnaire based on Bandura’s Social-Cognitive Theory was used. Data were analyzed using SPSS version 25 and Smart PLS software.Findings: The results indicated significant positive relationships between self-efficacy (β = 0.413, p = 0.001), moral disengagement (β = 0.596, p = 0.001), and attitudes (β = 0.653, p = 0.001) with the use of dietary supplements and performance enhancers among young Iraqi weightlifters.Conclusion: These athletes are influenced by a complex set of social-cognitive factors, including individual beliefs, social pressures, and misperceptions regarding the consequences of using dietary supplements and performance enhancers. Organizing educational and awareness programs focusing on the negative consequences of performance enhancers, ethical dimensions of their use, and healthier methods to enhance athletic performance appears to be essential.